News Deliverer on Twitter: News Organization and Individual Account Compared - Raidah Intizar Yusuf (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2018)
This study aims to determine the differences in the character of Twitter accounts from news organizations and individuals who practice citizen journalism on Twitter. The indicator used is the general aspect of a tweet: (1) profile picture, (2) profile name, (3) username, (4) message length, (4) full web link, (5) short web link, (6) compiled web link, (7) picture, (8) hashtag, (9) mention, (10) message content. The first three characteristics indicate the profile of a Twitter user who tweet the message, and the remaining indicates the message itself. Using a series of chi-squares, and independent t-test, the differences laid significantly on profile picture χ2(3, N = 40) = 26.14, p< .001, profile name χ2(3, N = 40) = 36.19, p< .001, username χ2(2, N = 40) = 36.19, p< .001, message length t (37)= -4.17, p< .001, 95% CI [-7.16, -2.48], short web link χ2(1) = 15, p< .001, mention χ2(1, N = 40) = 15.82, p< .001 and content χ2(2, N = 40) = 21.54, p< .001. Results shown news organization still have less horizontal communication to its audience, which can be detected by the lack of mentions. News tweets provided by individual account on the contrary employed interactive communication